Evaluasi Formatif: Perencanaan dan Penganggaran Responsif Gender (PPRG) Provinsi Kepulauan Riau - Safitri, Dian Prima; Edison, Edison (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2020)
This study examines the implementation of gender responsive budgeting planning at Kepulauan Riau Province through a formative evaluation approach. It is often understood that gender only prioritizes certain sexes. Policy holders and formulators in this case the Riau Islands Provincial Government undertook various strategies so that stakeholders are not gender biased, especially decision makers. One concept that supports PPRG is Gender equality which is one of the indicators of achievement in SDG’s. Integrating the PPRG agenda into the performance-based budget format (ABK) is a form of government movement to pursue the realization of gender equality to the local level. This study uses an exploratory approach to explore and fully respond to the dynamics of PPRG adaptation into the regional planning and budgeting system derived from programs and activities. The efforts of the Riau Islands Provincial Government to integrate PPRG by using a governance perspective where the focus on actors involved from the focal point elements in work units, academics, the private sector, community organizations to NGOs can be said to be successful. This is indicated by the Gender Development Index of the Riau Islands Province, which is ranked in the top 10 to be ranked 7th in Indonesia. Recommendations for implementing PPRG by maximizing the function of the coaching clinic for the preparation of the Gender Analysis Pathway (GAP) and the Gender Budget Statement (GBS)